Unraveling the Relationship Between Itching, Scratch Scales, and Biomarkers in Children With Alagille Syndrome. Issue 7 (26th May 2020) - Kamath, Binita M.; Spino, Cathie; McLain, Richard; Magee, John C.; Fredericks, Emily M.; Setchell, Kenneth D.; Miethke, Alexander; Molleston, Jean P.; Mack, Cara L.; Squires, Robert H.; Alonso, Estella M.; Murray, Karen F.; et al.
Abstract : Pruritus is a debilitating symptom for patients with Alagille syndrome (ALGS). In a previously reported trial of maralixibat, an investigational antipruritic agent, itching was assessed using a digital diary based on twice‐daily caregiver observation of itching severity (Itch Reported Outcome, ItchRO[Observer]). The goal of this study was to characterize pruritus in participants with ALGS at baseline in this trial, as assessed by the ItchRO instrument and the physician‐observed clinician scratch scale (CSS), relative to biomarkers putatively associated with pruritus and health‐related quality of life assessment. Thirty‐seven participants with ALGS (median age of 6 years; range 1‐17 years) were enrolled. No association was identified between CSS and ItchRO(Obs) ( r  = 0.22, P  = 0.2). Neither CSS nor ItchRO were associated with serum bile acids ( r  = −0.08, P  = 0.6 for both) or autotaxin ( r  = 0.22, P  = 0.2; r  = 0.28, P  = 0.12). There was no significant association between Pediatric Quality of Life Inventory total parent scores and CSS or ItchRO ( r  = −0.23, P  = 0.2; r  = −0.16, P  = 0.36). There was a significant association between ItchRO and Multidimensional Fatigue Scale and Family Impact Module total scores (Pearson correlation coefficient −0.575, P  = 0.0005; 0.504, P  = 0.002). In exploratory analysis, selected questions relating to fatigue and sleep disturbance (n = 12) from Pediatric Quality of Life Inventory, Multidimensional Fatigue Scale, and Family Impact Module were correlated with pruritus scores; positive associations were identified. Conclusion: Itching scores did not correlate with each other, nor with putative serum biomarkers of pruritus, and further, did not correlate with quality of life. Hypothesis‐generating analyses implicate sleep disturbance and fatigue as key associations with caregiver observations of itching. This is highly relevant to the selection of surrogate endpoints for clinical trials of pruritus therapies. Abstract : Itching scores did not correlate with each other, nor with putative serum biomarkers of pruritus, and did not correlate with quality of life. Hypothesis‐generating analyses implicate sleep disturbance and fatigue as key associations with caregiver observations of itching. This is highly relevant to the selection of surrogate endpoints for clinical trials of pruritus therapies.